Abscisic acid mediated differential growth responses of root and shoot of Vigna radiata (L.) Wilczek seedlings under water stress - Das, Satyajit (Plant physiology and biochemistry : PPB, 2018)
Copyright © 2017 Elsevier Masson SAS. All rights reserved.